2004
DOI: 10.1079/phn2004643
|View full text |Cite
|
Sign up to set email alerts
|

The nutritional status of asymptomatic HIV-infected Africans: directions for dietary intervention?

Abstract: Objective: To compare the relationships between food (nutrient) intakes and biochemical markers of nutritional status of asymptomatic HIV-infected with HIVuninfected subjects, to gain more information on the appropriate diet for HIV-infected persons at an early stage of infection. Design: Cross-sectional population-based survey. Setting: North West Province, South Africa. Subjects: Two hundred and sixteen asymptomatic HIV-infected and 1550 HIVuninfected men and women volunteers aged 15 years and older, recruit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 11 publications
0
23
0
Order By: Relevance
“…She showed that female-headed households, despite more limited resources, often attained better nutrition security, among other reasons because of fostering of social ties, networking and innovative informal sector activities to increase income. A comparison of the nutritional status of these asymptomatic infected subjects with uninfected subjects 12 showed no significant differences in nutrient intakes and anthropometric variables, but significantly lower levels of several biochemical variables indicative of nutritional status and higher levels of liver enzymes. A principal components analysis was used to summarise dietary patterns.…”
mentioning
confidence: 99%
“…She showed that female-headed households, despite more limited resources, often attained better nutrition security, among other reasons because of fostering of social ties, networking and innovative informal sector activities to increase income. A comparison of the nutritional status of these asymptomatic infected subjects with uninfected subjects 12 showed no significant differences in nutrient intakes and anthropometric variables, but significantly lower levels of several biochemical variables indicative of nutritional status and higher levels of liver enzymes. A principal components analysis was used to summarise dietary patterns.…”
mentioning
confidence: 99%
“…A decrease in nutritional intake is reflected in lower serum albumin concentrations. The association between serum albumin and alpha-tocopherol that reflects the nutritional status is well characterized (36), and could be invoked as one of the factors responsible for the decrease of alpha-tocopherol observed in this study. However, while a significant decrease in total protein concentrations was evident throughout the course of imatinib therapy, the decrease of serum albumin was less pronounced, and it is unlikely that nutritional factors are solely responsible for the decrease of alphatocopherol.…”
Section: Discussionmentioning
confidence: 96%
“…Studies have shown that the current physical activity guideline for adults of 25-30 minutes of moderate intensity physical activity daily would limit health risks for chronic diseases but would likely be insufficient for preventing weight gain [21,22]. Moreover, even if evidence exist that mild-to-moderate obesity is associated with reduced rates of mortality in HIV patients [29,30], its later consequences on health are far more severe than advantages [8,11,24].…”
Section: Discussionmentioning
confidence: 99%